Art & Heritage: An Ancient Image at our Doorstep (SIRJANĀ – A Journal Of Arts and Art Education, 2016)
For those interested in art, architectures, ancient temples and monumental remains, Nepal is an open museum. At every nook and corner there are temples with unique art/artistic creations to make outsiders wonder as to how they were crafted?